THE IMPORTANCE OF CHANGE MANAGEMENT IN COLLEGE ORGANIZATION - Najwa Khalishah Darmawan; Gabrielle Pulcheria Harefa, Marta Gloria, Elza Febriani Simatupang, Yani Zulfadila Putri (International Journal of Teaching and Learning, 2025)
Change management is crucial for college organizations to adapt and thrive in dynamic academic environments. With the rapid evolution of technology, globalization, and shifting student needs, colleges must implement structured approaches to managing change to ensure organizational resilience and effectiveness. Effective change management enables institutions to streamline processes, improve efficiency, and foster a culture of adaptability among faculty, staff, and students. One of the key reasons change management is essential in college organizations is its role in mitigating resistance. Transitioning to new systems, policies, or structures often leads to anxiety and resistance from stakeholders. A well-planned change management process can help address these concerns through clear communication, training, and active involvement. As John Kotter (2014), a renowned expert on leadership and change, noted, “Successful change relies on clear, credible, and convincing communication from leadership at every level of the organization.” Moreover, change management enhances decision-making processes and aligns organizational goals with the evolving needs of the academic community. By embedding a culture of continuous improvement, college organizations can remain competitive and innovative, ensuring long-term success in a rapidly changing landscape. Failure to manage change effectively can result in disengaged stakeholders, disrupted operations, and decreased overall performance, highlighting the critical need for structured change management strategies.